2022
DOI: 10.3389/fcvm.2022.822228
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Bypass Grafting Versus Percutaneous Coronary Intervention for Multivessel Coronary Artery Disease: A One-Stage Meta-Analysis

Abstract: Background and AimsData are emerging on 10-year mortality comparing coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI) with stenting for multivessel disease (MVD) without left main (LM) involvement. We conducted an updated two-stage meta-analysis using reconstructed individual patient data to compare long-term mortality between CABG and PCI for patients with MVD without significant LM coronary disease.MethodsMedline and Embase databases were searched for articles comparing CABG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
1
9
0
Order By: Relevance
“…in a number of parameters, including survival. At the same time, meta-analyses by Chew et al and Brown et al revealed the advantage of CABG over PCI in patients with multivessel disease and intermediate and high Syntax scores(25,26), and comparable results for individuals with low SS(26). Our study revealed a predominance in the frequency of MACCE in patients with intermediate SS who underwent PCI compared with those who underwent CABG (81 % and 50 %, re-…”
supporting
confidence: 74%
See 2 more Smart Citations
“…in a number of parameters, including survival. At the same time, meta-analyses by Chew et al and Brown et al revealed the advantage of CABG over PCI in patients with multivessel disease and intermediate and high Syntax scores(25,26), and comparable results for individuals with low SS(26). Our study revealed a predominance in the frequency of MACCE in patients with intermediate SS who underwent PCI compared with those who underwent CABG (81 % and 50 %, re-…”
supporting
confidence: 74%
“…For example, in our study, we retrospectively selected patients who underwent CABG or PCI under actual clinical conditions. Meanwhile, in recent meta-analyses (24)(25)(26)28) comprising RCTs in which the investigators compared the outcomes of PCI and CABG, disparate approaches were implemented to determine study endpoints, and a different composition of SS groups would have affected the authors' recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies, Lu et al 21 and Venuraju et al 22 did not report the HRs or 95% CI; hence, a web-based plot digitizing tool, WebPlotDigitizer, 23 was used to extract them from their respective Kaplan-Meier curves and reproduced them to obtain a HR using another software that reconstructs individual patient data from Kaplan-Meier curves, IPDfromKM. [24][25][26] An example of how this was done is demonstrated in the Supplemental Methods.…”
Section: Se =mentioning
confidence: 99%
“…With the advancement of the PCI, such as the design of stents, higher-risk patients with more complex coronary lesions have been included in trials [ 24 ]. As such, we found relative mortality benefits of CABG over PCI in this study, especially in patients with multivessel CAD.…”
Section: Reviewmentioning
confidence: 99%